User-Centric Innovation District Planning: Lessons from Brisbane’s Leading Innovation Districts - Niusha Esmaeilpoorarabi; Tan Yigitcanlar (Buildings, 2023)
Innovation districts are widely known as an effective land use type for fostering and sustaining knowledge and innovation economy growth in cities. Knowledge workers and the public are among the main stakeholders and key drivers for the growth of innovation districts. However, these groups’ needs are often not well considered in the top-down implementation of innovation districts. This paper aims to explore the user preferences and decision makers’ perspectives in innovation district planning, design, and development. The study tackles the question of which characteristics fulfil the responsibility of innovation districts toward both societies (reflecting user preferences) and cities (reflecting decision makers’ perspectives). As for the methodology, a case study approach was employed to collect the required data from three innovation districts in Brisbane, Australia. The data are qualitatively and quantitatively analysed. The analysis findings highlighted the similarities between user preferences and decision makers’ perspectives—e.g., usefulness of decentralisation, urbanism, mixed-use development, street life, and social interactions in innovation districts—and the differences that need to be carefully factored into the planning, design, and development of innovation districts with a user-centric approach.